LONG NONCODING RNA UPREGULATES ADAPTER SHCA PROTEIN EXPRESSION TO PROMOTE COGNITIVE IMPAIRMENT AFTER CARDIAC ARREST AND RESUSCITATION. Issue 2 (26th July 2022) - Zhang, Yu-Han; Peng, Fei; Zhang, Lu; Kang, Kang; Yang, Man; Chen, Chan; Yu, Hai
ABSTRACT: Aim: More patients are resuscitated from cardiac arrest and cardiopulmonary resuscitation (CA/CPR) due to advances in medical care. However, the burden now lies with post–cardiac arrest cognitive impairment in CA/CPR survivors. Based on our previous study, we aimed to further confirm the correlation between the long noncoding RNA-promoting ShcA (lncRNA-PS)/Src homology and collagen A (ShcA) axis and CA/CPR-induced cognitive impairment in molecular, cellular, and tissue levels. Methods and Results: The in vivo experiments were based on a mouse model of CA/CPR, while oxygen-glucose deprivation and reoxygenation was used as a cell model in vitro. Conditional ShcA suppression in neurons of the hippocampal CA1 region was achieved by cyclization recombinase of bacteriophage P1 recognizing DNA fragment locus of x-over P1 site (Cre/LoxP recombination system). Genetic manipulation of HT22 was achieved by lentivirus targeting lncRNA-PS and ShcA. Neurological function score was remarkably decreased, and cognitive function was affected after restoration of spontaneous circulation. LncRNA-PS and ShcA overexpression after CA/CPR, mainly happened in neurons of hippocampal CA1 region, was observed by in situ hybridization and immunofluorescence. Neuronal ShcA knockdown in hippocampal CA1 region before CA/CPR attenuated cognitive impairment after CA/CPR. ShcA deficiency protected HT22 cell line against oxygen-glucose deprivation and reoxygenation by inhibiting inflammation and apoptosis. In vitro upregulation of lncRNA-PS elevated ShcA expression, which was reversed by knockdown of ShcA. Conclusions: This study revealed that lncRNA-PS/ShcA axis is critically involved in the pathogenesis of cognitive impairment after CA/CPR. By inhibiting ShcA expression in neurons of the hippocampal CA1 region could improve the survival outcomes in mice after CA/CPR.